The California Elected Women's Association for Education and Research Newsletter (1976)
The Summer 1976 CEWAER (California Elected Women's Association for Education and Research) newsletter announces new leadership under President Anne Rudin and reports receipt of a $5,000 foundation grant to support the organization's educational and leadership activities. It celebrates a strong year for women candidates statewide, listing numerous CEWAER members and other women running for Congress, State Senate, Assembly, and county offices. The newsletter outlines upcoming conferences, including "Winning in the 70's!" in Sacramento and a League of Cities panel on whether women bring distinct management and political styles. It also promotes a training course, "Planning to Run for Office: Issues Facing the Woman Candidate," designed to equip women with campaign and leadership skills.